2022
DOI: 10.5751/ace-02253-170228
|View full text |Cite
|
Sign up to set email alerts
|

Survival of translocated Columbian Sharp-tailed Grouse: recognizing trends in post-release mortality to improve reintroductions

Abstract: Survival of translocated prairie-grouse (Tympanuchus spp.) is often low in the first few weeks or months following release into a novel environment. Understanding the processes and mechanisms that influence short-term, post-release survival, such as Allee effects (i.e., inverse density dependence), or individual characteristics of translocated individuals (e.g., age, sex) is imperative for designing successful translocation programs. Additionally, identifying timeframes during which translocated individuals ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Of all released birds, 13.1% died (n = 54) and 9.7% went missing (n = 40) within the first 2 weeks after release, indicating potentially substantial mortality associated with the act of translocation, adjustment to the new environment, and dispersal movement after translocation (Teige et al, 2023). High initial mortality rates are not unprecedented among prairie grouse translocations; Mathews et al (2022) found similar rates of mortality (0.992 daily survival) within the first 40 days after Columbian sharp-tailed grouse (Tympanuchus phasianellus columbianus) translocation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of all released birds, 13.1% died (n = 54) and 9.7% went missing (n = 40) within the first 2 weeks after release, indicating potentially substantial mortality associated with the act of translocation, adjustment to the new environment, and dispersal movement after translocation (Teige et al, 2023). High initial mortality rates are not unprecedented among prairie grouse translocations; Mathews et al (2022) found similar rates of mortality (0.992 daily survival) within the first 40 days after Columbian sharp-tailed grouse (Tympanuchus phasianellus columbianus) translocation.…”
Section: Discussionmentioning
confidence: 99%
“…High initial mortality rates are not unprecedented among prairie grouse translocations; Mathews et al. ( 2022 ) found similar rates of mortality (0.992 daily survival) within the first 40 days after Columbian sharp‐tailed grouse ( Tympanuchus phasianellus columbianus ) translocation.…”
Section: Discussionmentioning
confidence: 99%
“…Spring translocated Gunnison sage‐grouse had lower survival during the first 75 days following release than during the remainder of the first year (Apa et al 2022). Similarly, translocated Columbian sharp‐tail grouse had a survival rate of 42% for adults and 67% for yearlings during the breeding season, with substantially greater mortality for the 40‐50 days after release (Mathews et al 2016, 2022). Within the breeding season, we found adult survival was lowest the third week of April, and was lower than survival estimates for females during that week in nontranslocated birds (~0.92; Plumb 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Radio and satellite telemetry are widely used to study movement and demographics of gallinaceous birds including greater sage‐grouse ( Centrocercus urophasianus ; Gibson et al 2013, Severson et al 2019, Olsen et al 2021a, Mathews et al 2022, Schuyler et al 2022). Sage‐grouse have experienced pronounced range contractions and population declines, have twice been petitioned for listing under the Endangered Species Act (U.S.…”
mentioning
confidence: 99%